Rare case of vaginal leiomyoma in an adolescent girl: a diagnostic dilemma - Upadhyay, Manisha; Chauhan, Meenakshi; Gautam, Sarika; Yadav, Tek Chand (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Vaginal leiomyoma are very uncommon primary tumors of vagina. They are extremely rare in adolescent age group. They can have variable clinical presentations and could be difficult to diagnose at times in adolescents. We report an extremely rare and novel case of primary vaginal leiomyoma with hyaline degeneration in an adolescent girl which was primarily misdiagnosed as hematocolpos or vaginal malignancy due to its clinical presentation. A 14-year-old girl presented with complains of difficulty in passing urine and irregular vaginal bleeding. On per rectal examination an ill-defined bulge was felt anteriorly and altered chocolate color blood was coming out of vagina. Her ultrasonography report was suggestive of a cervicovaginal mass or hematocolpos. So, examination under anesthesia (EUA) was planned with probable diagnosis of hematocolpos due to secondary reasons or malignancy. On EUA a soft cystic vaginal mass was felt arising from the anterolateral wall obscuring the cervical os and cervix was felt behind it separately. Biopsy was taken from the mass which was confirmed histopathologically and immunohistochemically as vaginal leiomyoma with hyaline degeneration. Patient was managed successfully with complete tumor resection through vaginal approach followed by vaginal reconstruction. Though rare but the differential diagnosis of vaginal leiomyoma should always be kept in mind in adolescent girls presenting with vaginal mass and abnormal vaginal bleeding. Primary vaginal leiomyoma can be completely cured by surgery if diagnosed timely and appropriately so, should never be missed in adolescent age group.